Bernhard Nocht Institute of Hamburg and ten illustrious Venezuelans who went through it - Luis Eduardo Traviezo Valles (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
The Institute for Naval and Tropical Diseases (Institute for Maritime and Tropical Diseases) begins its activities in Hamburg, Germany, on October 1, 1900, as a result of the fifth cholera pandemic (1892) that had affected more than 17,000 people , killing 9,000 of them, which motivated the authorities to its creation